Association of α-1-Antichymotrypsin Expression with the Development of Conformational Changes of Tau Protein in Alzheimer's Disease Brain - Horta-López, Perla H; Mendoza-Franco, Graciela; Rodríguez-Cruz, Fanny; Torres-Cruz, Francisco M; Hernández-Echeagaray, Elizabeth; Jarero-Basulto, Jose J; Rícny, Jan; Florán Garduño, Benjamín; Garcia-Sierra, Francisco (Neuroscience, 2023)
In Alzheimer's disease (AD), two mutually exclusive amino-terminal-dependent conformations have been reported to occur during the aggregation of Tau protein into neurofibrillary tangles (NFTs). An early conformation of full-length Tau, involving the bending of the amino terminus over the third repeated domain, is recognized by the Alz-50 antibody, followed by a second conformation recognized by Tau-66 antibody that depends on the folding of the proline-rich region over the third repeated domain in a molecule partially truncated at the amino- and carboxyl-termini. α-1-antichymotrypsin (ACT) is an acute phase serum glycoprotein that accumulates abnormally in the brain of AD patients, and since it is considered to promote the in vitro and in vivo aggregation of amyloid-β, we here seek further evidence that ACT may also contribute to the abnormal aggregation of Tau in AD. By analyzing brain samples from a population of AD cases under immunofluorescence and high-resolution confocal microscopy, we demonstrate here the abundant expression of ACT in hippocampal neurons, visualized as a granular diffuse accumulation, frequently reaching the nuclear compartment. In a significant number of these neurons, intracellular NFTs composed of abnormally phosphorylated and truncated Tau at Asp421 were also observed to coexist in separated regions of the cytoplasm. However, we found strong colocalization between ACT and diffuse aggregates of Tau-66-positive granules, which was not observed with Alz-50 antibody. These results suggest that ACT may play a role during the development of Tau conformational changes facilitating its aggregation during the formation of the neurofibrillary pathology in AD.
Keywords: Neurons; α-1-antichymotrypsin; neurofibrilární klubka; tau Proteins; Neurofibrillary Tangles; proteiny tau; Antibodies; protilátky; Alzheimer’s disease; neurofibrillary tangles; Alzheimer Disease; mozek; Tau conformation; Brain; Humans; neurony; immunofluorescence; Alzheimerova nemoc; lidé